Identifying misbonded atoms in the 2019 CoRE metal–organic framework database. Issue 45 (20th July 2020) - Chen, Taoyi; Manz, Thomas A.
Abstract : The 2019 CoRE MOF database was cleaned by identifying structures containing isolated atoms, overlapping atoms, misplaced hydrogens, and under/over-bonded carbons. Abstract : Databases of experimentally-derived metal–organic framework (MOF) crystal structures are useful for large-scale computational screening to identify which MOFs are best-suited for particular applications. However, these crystal structures must be cleaned to identify and/or correct various artifacts. The recently published 2019 CoRE MOF database (Chung et al., J. Chem. Eng. Data, 2019, 64, 5985–5998) reported thousands of experimentally-derived crystal structures that were partially cleaned to remove solvent molecules, to identify hundreds of disordered structures (approximately thirty of those were corrected), and to manually correct approximately 100 structures ( e.g., adding missing hydrogen atoms). Herein, further cleaning of the 2019 CoRE MOF database is performed to identify structures with misbonded or isolated atoms: (i) structures containing an isolated atom, (ii) structures containing atoms too close together ( i.e., overlapping atoms), (iii) structures containing a misplaced hydrogen atom, (iv) structures containing an under-bonded carbon atom (which might be caused by missing hydrogen atoms), and (v) structures containing an over-bonded carbon atom. This study should not be viewed as the final cleaning of this database, but rather as progress along the way towards the goal of someday achieving a completely cleaned set of experimentally-derived MOF crystal structures. We performed atom typing for all of the accepted structures to identify those structures that can be parameterized by previously reported forcefield precursors (Chen and Manz, RSC Adv ., 2019, 9, 36492–36507). We report several forcefield precursors ( e.g., net atomic charges, atom-in-material polarizabilities, atom-in-material dispersion coefficients, electron cloud parameters, etc. ) for more than five thousand MOFs in the 2019 CoRE MOF database.